Local Food Consumption Value Towards Food Destination Image in Sarawak: The Moderating Impact of Food Satisfaction - Leow, Hui Ting; Abang Azlan, Mohamad; Lo, May Chiun; Ramayah, T.; Chin, Ying Sin (Institute for Tourism, 2024)
This study explores the role of local food consumption in enhancing Sarawak's image as a food destination, focusing on the moderating impact of food satisfaction. Drawing on a cross-sectional analysis using a selfadministered questionnaire, the study investigates the influence of taste and quality value, health value, price value, emotional value, and prestige value on the food destination image. The sample consists of 181 tourists who visited Sarawak, providing insights into visitors' diverse perspectives and preferences. The data was further analysed using SPSS 28.0 and WarpPLS 8.0. The findings reveal that taste, quality, health, emotional, and prestige value significantly affect the food destination image. However, the study has shown that price value has no significant impact. Surprisingly, food satisfaction does not moderate the relationship between local food consumption value and food destination image. Theoretical implications highlight the need for a more comprehensive understanding of the factors shaping consumers' perceptions. In contrast, practical implications suggest strategic considerations for culinary destinations in marketing campaigns and pricing strategies. Overall, this study contributes valuable insights for destination marketers aiming to attract tourists interested in unique culinary experiences and enhance their overall perception of the destination